Vowel distribution and hyper-articulation in Singaporean bilinguals - Lin, Hannah Shi Hui (Nanyang Technological University, 2021)
There have been many studies documenting the differences in vowel categorical perception and speech production between bilinguals and monolinguals, with a general underlying finding that the developmental pathway for vowel categorization in bilingual speakers is markedly different from monolingual speakers, possibly stemming from interactions between phonetic systems of the first language and the second language, as first posited by Flege’s Speech Learning Model (Flege, 1995). This paper aims to provide a descriptive exploratory study into how vowel space distribution differs between languages within the same bilingual speaker in adult-directed speech in the main languages of Singapore – English and Mandarin. This will be achieved through comparing first and second formant measurements for /i/, /a/ and /u/ between languages within English-Mandarin bilingual speakers. Additionally, this paper will also discuss vowel hyper-articulation in the context of bilingual parents. Vowel hyper-articulation is a universal component of infant-directed speech that has been found to occur cross-culturally and cross-linguistically, manifested by exaggerated articulatory gestures resulting in an expansion of vowel triangle area when caregivers talk to their infants. While there has been many studies corroborating this effect in monolingual speakers, there is a dearth of studies exploring vowel hyper-articulatory effects in bilingual speakers. Thus, this paper aims to address if vowel hyper-articulation occurs to the same degree in both languages for bilingual caregivers, measured through inflation rates computed within each language.